Body-weight supported sprint running - an effective method to generate reduced ground contact times in well trained sprinters - Kratky, S.; Müller, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Time on the ground is the crucial part of sprinting as the available time frame to apply force to the ground diminishes with increasing running velocity (Mero et al. 1992; Weyand et al. 2000). Data of elite sprinters indicate that faster athletes realize shorter ground contact times compared to slower individuals (Mann 2010). The aim of this study was to investigate effects of body-weight support during full-effort sprints and overspeed sprints on kinematic stride parameters and especially ground contact time in 19 Austrian male elite sprinters. Methods: A kite with a lifting effect combined with a towing system to erase drag was utilized. Subjects performed flying 20m-sprints under three conditions: (1) free sprint; (2) body-weight supported sprint - normal speed (BWS-NS); and (3) body-weight supported sprint - overspeed (BWS-OS). Sprint cycle characteristics were recorded during the high-speed phase by an optical acquisition system. One-way analyses of variance for repeated measures were used to determine differences between sprinting conditions and partial Eta-squared was used to determine effect-size (ES). Results: Compared to the free sprint, running velocity, step length, and step frequency remained unchanged during BWS-NS, while ground contact time decreased (-5.80%, p<0.001, ES=0.85) and air time increased (+5.79%, p<0.001, ES=0.79). Throughout BWS-OS ground contact time (-7.66%, p<0.001, ES=0.85) was reduced, whereas running velocity (+2.72%, p<0.001, ES=0.91), air time (+4.92%, p<0.001, ES=0.72), step length (+1.98%, p<0.001, ES=0.58) and step frequency (+1.05%; p<0.01, ES=0.39) increased. Compared to BWS-NS, BWS-OS caused an increase in running velocity (+3.33%, p<0.001, ES=0.94), step length (+1.92%, p<0.001, ES=0.62), and step frequency (+1.37%, p<0.01, ES=0.39), while ground contact time was diminished (-1.97%, p<0.001, ES=0.48). Discussion: In summary, sprinting with a body-weight supporting kite appeared to be a highly specific method to reduce ground contact times in well trained sprinters. The additional application of an overspeed condition led to a further reduction of ground contact time. Therefore, we recommend body-weight supported sprinting as an additional tool in sprint training.